2000
DOI: 10.1093/ps/79.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the stocking density and rearing season on incidence of sudden death syndrome in broiler chickens

Abstract: Influences of the stocking density and rearing season on the incidence of sudden death syndrome (SDS) were investigated in commercial broiler chickens, which were reared until 63 d after birth. The SDS mortality and total mortality were measured at three different stocking densities of 12, 15, and 18 birds/m2 in rearing seasons of summer, autumn, and winter. At stocking densities of 15 and 12 birds/m2, neither SDS mortality nor total mortality was significantly different throughout the rearing season. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 13 publications
4
19
0
3
Order By: Relevance
“…If birds are not able to feed to the extent they are motivated this may lead to frustration and impaired welfare. However, several other studies found either no response of feed intake to density (de Oliveira et al, 2000;Imaeda, 2000;McLean et al, 2002;Ravindran et al, 2006;Sirri et al, 2007;Turkyilmaz, 2008), an increase in feed intake with increasing density (Zuowei et al, 2011), or peak values at intermediate densities (Feddes et al, 2002). In line with the 2000 report, several authors found that feed intake decreased with increasing density (Al Bokkers and Koene, 2004;Thomas et al, 2004;Dozier et al, 2005;Villagra et al, 2009;Beloor et al, 2010;Benyi, 2012).…”
Section: Stocking Density Feed Intake and Feed Conversionmentioning
confidence: 77%
See 1 more Smart Citation
“…If birds are not able to feed to the extent they are motivated this may lead to frustration and impaired welfare. However, several other studies found either no response of feed intake to density (de Oliveira et al, 2000;Imaeda, 2000;McLean et al, 2002;Ravindran et al, 2006;Sirri et al, 2007;Turkyilmaz, 2008), an increase in feed intake with increasing density (Zuowei et al, 2011), or peak values at intermediate densities (Feddes et al, 2002). In line with the 2000 report, several authors found that feed intake decreased with increasing density (Al Bokkers and Koene, 2004;Thomas et al, 2004;Dozier et al, 2005;Villagra et al, 2009;Beloor et al, 2010;Benyi, 2012).…”
Section: Stocking Density Feed Intake and Feed Conversionmentioning
confidence: 77%
“…It is therefore highly relevant to discuss reduced feed intake and the causes of this reduction in poultry production. Evidence on food conversion ratios is similarly contradictory, with some studies indicating worse (i.e., higher) ratios at higher density (Dozier et al, 2005;Dozier et al, 2006); (Sirri et al, 2007;Zuowei et al, 2011), whilst others found no effect (Imaeda, 2000;McLean et al, 2002;Thomas et al, 2004;Turkyilmaz, 2008;Villagra et al, 2009;Beloor et al, 2010;Petek et al, 2010;Sekeroglu et al, 2011) or even an improved ratio (de Oliveira et al, 2000). However, several other studies found either no response of feed intake to density (de Oliveira et al, 2000;Imaeda, 2000;McLean et al, 2002;Ravindran et al, 2006;Sirri et al, 2007;Turkyilmaz, 2008), an increase in feed intake with increasing density (Zuowei et al, 2011), or peak values at intermediate densities (Feddes et al, 2002).…”
Section: Stocking Density Feed Intake and Feed Conversionmentioning
confidence: 99%
“…The hottest periods o f the year have raised mortality rates from sudden death syndrome (IMAEDA, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This status may be aggravated by a collapse in the balance of electrolytes, which would affect bird's ability of supplying these components to vital cardiac outputs in order to survive, added to the incidence of arrhythmias (IMAEDA, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…A plausible explanation might be the lack of mitigating factors, because other production parameters such as temperature and stocking density were normal, as the experiment was conducted in a university research farm. Imaeda (20) reported significantly higher mortality at higher stocking density in summer when compared with a lower stocking density in winter and autumn. In commercial broiler farms, high stocking density is common for economic reasons and such management systems could act as a mitigating factor or trigger in predisposing animals to SDS.…”
Section: Resultsmentioning
confidence: 92%